Peran Lembaga Artha Dalam Meningkatkan Kesejahteraan Masyarakat Hindu (Studi Kasus Koperasi Dharmawangsa) - Titin Sutarti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
Hindu society is an integral part that is inseparable from the people of the nation of the archipelago, in which there are many potential resources that must be empowered. The difference in all meaning and meaning is a foothold / source of intuition which is the spirit of all Hindu community / institutions in determining a policy and concrete actions. The potential of resources inspired by Arthasastra will bring a commitment and strength to advance the life of Hindu society in a planned, programmed, comprehensive and sustainable manner, namely the formation of artha institutions capable of protecting people's lives. The presence of the Artha Institute as one of the pillars supporting the advancement of community / community life is a necessity that cannot be denied. Factor of poverty, emergency needs that must get funding quickly and easily are needed by Hindus. Difficult access to find loans in the Bank for the benefit of consumption and health causes the importance of Hindu artha institutions to sustain the needs of these Hindus. Seeing such phenomena, Hindus must be able to educate themselves by responding to a challenge as an opportunity and an difficulty as an opportunity that must be immediately addressed and acted upon along with the development and changing times that lead to the establishment of culture and civilization, so even though small in terms the number of people does not need to worry because nature will select and favor the quality. This research is a type of qualitative research by referring to the sociological aspects that occur in the life of Hindus. To discuss this phenomenon researchers use Functional Theory and Role Theory. As for data collection techniques using methods observation, literature, interviews and documentation.Furthermore, the results of this study explain that the Functions of the Dharmawangsa Cooperative Institution, namely: contribute to running the economy, developing the Indonesian economy based on the people as the owner and its users, preventing economic capitalization, as the welfare of the community, especially its members. While the role of the Dharmawangsaya cooperative is a. internal role: creativity of problem solving and decision making, maintenance of cooperative administration and cooperative efforts, strengthen networks, expand membership, strengthen finance, increase management resources, optimize management tasks, take responsibility for organizational activities, b. external role: forming an organization's information center, improving the communication and coordination functions of the people, preparing loan funds